2007
DOI: 10.54207/bsmps1000-2007-5wic42
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of Kail pine (Pinus wallichiana) seedlings to various ectomycorrhizal fungi

Abstract: The response of 10 locally isolated ectomycorrhizae belonging to 9 genera alongwith 2 unidentified ones was assessed in in vitro for mycorrhizal colonization and plant growth in Kail pine (Pinus wallichiana). The studies revealed that typical ectomycorrhizae were established on inoculated plants within 3-4 weeks of inoculation. Maximum plant height and better mycorrhizal root colonization was noticed by Pisolithus tinctorius followed by Hebeloma crustuliniforme and Suillus sp. isolate 2. Maximum shoot and root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Thereafter several studies have observed EcM association with this tree species [21,[61][62][63][64][65][66][67][68][69][70][71][72][73]. Moreover, many researchers have successfully synthesized Rhizopogon ectomycorrhizae with several conifer species under laboratory conditions [25,[74][75][76][77][78][79][80][81][82][83], beside this, the seedlings of C. deodara have been inoculated with pure cultures of several EcM fungi other than Rhizopogon sp [84][85][86][87]. However, there have been relatively very few studies confirming in vitro synthesis between R. himalayensis and C. deodara seedlings [25,83] and needs more research to characterize this association with the roots C. deodara growing in pure forests.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter several studies have observed EcM association with this tree species [21,[61][62][63][64][65][66][67][68][69][70][71][72][73]. Moreover, many researchers have successfully synthesized Rhizopogon ectomycorrhizae with several conifer species under laboratory conditions [25,[74][75][76][77][78][79][80][81][82][83], beside this, the seedlings of C. deodara have been inoculated with pure cultures of several EcM fungi other than Rhizopogon sp [84][85][86][87]. However, there have been relatively very few studies confirming in vitro synthesis between R. himalayensis and C. deodara seedlings [25,83] and needs more research to characterize this association with the roots C. deodara growing in pure forests.…”
Section: Discussionmentioning
confidence: 99%